A branch‐and‐cut algorithm for the ring spur assignment problem. Issue 2 (28th January 2013) - Fortz, B.; Carroll, Paula; Fortz, Bernard; Labbé, Martine; McGarraghy, Seán; Gouveia, Luis; Voß, Stefan
Abstract The ring spur assignment problem arises in the design of next‐generation telecommunications networks and has applications in location‐allocation problems. The aim is to identify a minimum cost set of interconnected ring spurs. We seek to connect all nodes of the network either on a set of bounded disjoint local rings or by a single spur edge connected to a node on a local ring. Local rings are interconnected by a special ring called the tertiary ring. We show that the problem is NP ‐Hard and present an Integer Programming formulation with additional valid inequalities. We implement a branch‐and‐cut algorithm and present our conclusions with computational results. © 2013 Wiley Periodicals, Inc. NETWORKS, 2013